ESTIMATION OF CARBON POTENTIAL ABOVE THE GROUND AT THE STAND LEVEL POLES AND TREES IN FOREST CITY PEKANBARU - Sakinah Lubis; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The process of increasing temperature in the atmosphere or global warming is a climate change that has always been environmental problems. Related to the phenomenon of climate change, plants have an important role because it can absorb and store carbon as biomass through sequestration mechanism. Pekanbaru is a tropical city and it has temperature is high. The forest city areas as a green open space has a very large role in lowering the air temperature and tackling global warming. This research aimed to estimate the magnitude of the potential of biomass carbon in the area of forest city in ​​Pekanbaru. The result of this research is expected data the magnitude of potential carbon content above ground level on the forest. This research only measured the carbon content above ground level of poles and tree stands. Measures of conducted the measurement of Diameter Breast Height (DBH) and the identification of tree species. The results showed the magnitude of the potential of biomass carbon in the areas of forest city in Pekanbaru is 59.929 tons / ha or 366.166 tons when extrapolated to the total area of forest city Pekanbaru is ​​6.11 ha. Keywords: Forest, carbon, biomass